Kreacja postaci kobiecej w "Chamie" Elizy Orzeszkowej = Creation of female charakter in Eliza Orzeszkowa`s "Cham" - Zacharkiewicz, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article raises the issue of characters creation methods in Eliza Orzeszkowa`s "Cham". It is discusses scientific methods used by an author: physiognomy and researches from psychiatry area. Study about both of them suggested that creation of characters is schematic but also contain psychological truth. Analysis of character development factors and the comparison her to the others characters in novel leads to the conclusion of her reliability.
Keywords: Orzeszkowa, Eliza (1841-1910) - twórczość; postać literacka